1991
DOI: 10.1111/j.1365-2427.1991.tb00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food concentration on the carbon balance of Bosmina longirostris (Crustacea: Cladocera)

Abstract: 1. The carbon balance of the small cladoceran, Bosmina longirostris, was examined at four food concentrations (0.05, 0.10, 0.25, 2.50mg C I" ) based on long-term growth experiments.2. At birth, B. longirostris allocated about 60% of assimilation to body growth at all food concentrations. However, allocation to body growth decreased with age and was less than 5% after the fourth instar at the lowest food concentration. The proportion allocated to reproduction increased with increasing food concentration, but wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
(48 reference statements)
1
17
0
2
Order By: Relevance
“…In Bosmina, for example, Urabe (1991) found consistent increases in L with food level (0.05, 0.1, 0.25 and 2.5 mg C l -1 ) in seven to eight successive postneonatal instars. About 60% of total assimilate was allocated to Gs at birth, but declined in subsequent instars (to \5% in instar IV at the lowest food).…”
Section: Clonal and Genotypic Differences In Body Sizementioning
confidence: 72%
See 1 more Smart Citation
“…In Bosmina, for example, Urabe (1991) found consistent increases in L with food level (0.05, 0.1, 0.25 and 2.5 mg C l -1 ) in seven to eight successive postneonatal instars. About 60% of total assimilate was allocated to Gs at birth, but declined in subsequent instars (to \5% in instar IV at the lowest food).…”
Section: Clonal and Genotypic Differences In Body Sizementioning
confidence: 72%
“…In Bosmina, carapace length in 7 or 8 successive instars was consistently greater at food levels of 0.05, 0.1, 0.25 and 2.5 mg C l -1 (Urabe, 1991), with similar positive influences of food supply on body size evident in Diaphanosoma and Moina (e.g. Sipaȗba-Tavares & Bachion, 2002).…”
Section: Body Size In Relation To Extrinsic Resourcesmentioning
confidence: 77%
“…It is said that protozoans transfer a large portion of the energy ingested as food from the trophic level below to the predator level as protozoan biomass . However reported gross growth efficiencies of ciliates reported (Verity, 1985) were not necessarily higher than those of Bosmina (Urabe, 1991) .…”
Section: Carbon Flow In Two Fish Culture Pondsmentioning
confidence: 87%
“…The assumed taxon specificity is the only generalization on GGE of planktonic organisms used in these models. Individual studies have shown that GGE will depend on food concentration (Verity 1985;Urabe 1991), temperature (Sherr et al 1983;Rassoulzadegan 1982), and food quality. One aspect of food quality, the effect of relative prey size on GGE, has not yet been addressed systematically in individual studies.…”
Section: Acknowledgmentsmentioning
confidence: 99%